ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35/PUU-X/2012 DALAM MEMBERIKAN KEDUDUKAN DAN PERLINDUNGAN TERHADAP HUTAN ADAT - Nur Fitri, Ragil Meiliana; Ummul Firdaus, Sunny (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2024)
This study describes and examines the problem regarding the customary forest was released from its status as a national forest ; as well as how is the analysis and impact after the Constitutional Court decision number 35/PUU-X/2012 in giving position and protection of customary forests. This research uses a type of doctrinal (normative) research that is prescriptive. Types and sources of legal materials include primary and secondary legal materials. The legal material collection technique used is library research. Furthermore, the legal material analysis technique used with the syllogism method uses a deductive mindset. The results of the study show that the Constitutional Court Decision Number 35/PUU-X/2012 has changed the status of customary forest from state forest to private forest to provide legal certainty and justice for customary law communities as subjects who inhabit customary forest areas. Furthermore, after the decision was made, it had an impact on the central government to implement it through the Minister of Environment and Forestry Regulation No. 32 of 2015 concerning Private Forests, and the Regional Government implements it through the preparation of Regional Regulations related to the recognition of the existence of Customary Forests and Customary Law Communities. However, the implementation has not run optimally, as evidenced by the existence of several cases of disputes over customary forests in Indonesia. Penelitian ini mendiskripsikan dan mengkaji permasalahan, pertama mengapa hutan adat dilepaskan statusnya sebagai hutan negara oleh Kedua, bagaimana analisis serta dampak pasca adanya putusan Mahkamah Konstitusi nomor 35/PUU-X/2012 dalam memberikan kedudukan dan perlindungan terhadap hutan adat. Penelitian ini menggunakan jenis penelitian doktrinal (normatif) bersifat preskriptif. Jenis dan bahan sumber bahan hukum meliputi bahan hukum primer dan sekunder. Teknik pengumpulan bahan hukum yang digunakan adalah studi kepustakaan. Selanjutnya Teknik analisis bahan hukum yang digunakan dengan metode silogisme menggunakan pola pikir deduktif. Hasil penelitian menunjukkan bahwa Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 telah merubah status hutan adat dari hutan negara menjadi hutan hak untuk memberikan kepastian dan keadilan hukum bagi masyarakat hukum adat sebagai subjek yang mendiami kawasan hutan adat. Selanjutnya pasca ada putusan tersebut membawa dampak bagi pemerintah pusat untuk mengimplementasikannya melalui Peraturan Menteri Lingkungan Hidup dan Kehutanan No. 32 tahun 2015 tentang Hutan Hak, dan Pemerintah Daerah mengimplementasikan melalui penyusunan Peraturan Daerah terkait dengan pengakuan keberadaan Hutan Adat dan Masyarakat Hukum Adat. Namun dalam implementasinya belum berjalan dengan maksimal, dibuktikan dengan masih adanya beberapa kasus sengketan hutan adat di Indonesia.